2007
DOI: 10.1037/1045-3830.22.4.511
|View full text |Cite
|
Sign up to set email alerts
|

Confirmatory factor structure of the Kaufman Assessment Battery for Children--Second Edition: Consistency with Cattell-Horn-Carroll theory.

Abstract: is a departure from the original KABC in that it allows for interpretation via two theoretical models of intelligence. This study had two purposes: to determine whether the KABC-II measures the same constructs across ages and to investigate whether those constructs are consistent with Cattell-Horn-Carroll (CHC) theory. Multiple-sample analyses were used to test for equality of the variancecovariance matrices across the 3-to 18-year-old sample. Higher-order confirmatory factor analyses were used to compare the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 24 publications
7
66
0
Order By: Relevance
“…Although this is in line as the sole measure of cognitive ability. The different subscales of this measure are difficult to interpret which lowers the validity of both subscales [54,55]. However, since the total score for cognitive ability (Mental Processing Composite) was the main outcome of this study, the interpretation of the subscales might be less important.…”
Section: Discussionmentioning
confidence: 95%
“…Although this is in line as the sole measure of cognitive ability. The different subscales of this measure are difficult to interpret which lowers the validity of both subscales [54,55]. However, since the total score for cognitive ability (Mental Processing Composite) was the main outcome of this study, the interpretation of the subscales might be less important.…”
Section: Discussionmentioning
confidence: 95%
“…They found five broad ability factors were reliably identified as distinct providing evidence that preschool cognitive ability can be interpreted through CHC theory. Research on the KABC-II (Reynolds, et al, 2007) indicated the instrument measures the same constructs across the ages (3 to 18), and the factor structure is closely aligned with the CHC model. Additionally, the theories included in the CHC model have been validated across gender and ethnic groups (Carroll, 1993;Horn & Noll, 1997).…”
Section: Empirical Support For the Chc Modelmentioning
confidence: 98%
“…One objective of the present study was to determine if African American and Caucasian preschool children displayed similar patterns among the CHC factors on the KABC-II. Past research has shown the KABC-II adequately assesses multiple CHC abilities in preschool children (Hunt, 2007;Morgan, 2008;Reynolds, et al, 2007). Research also indicated the CHC factor structure is invariant across ethnic groups (Edwards & Oakland, 2006).…”
Section: Follow-up Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The KABC-II is based on the Cattell-Horn-Carroll (CHC) model of cognitive abilities (A. S. Kaufman & Kaufman, 2004; see also Reynolds, Keith, Goldenring-Fine, Fisher, & Low, 2007). The CHC theory integrates the Cattell-Horn Gf-Gc theory (distinguishing between various fluid and crystallized cognitive abilities) and Carroll's three-stratum theory (Carroll, 1993;McGrew, 2005).…”
Section: Generalizability Of Cognitive Structurementioning
confidence: 99%